**on putting x=4,y= ^{-}5 in the equation 3x-2y-2k=0 then the value of k is wat**

**Given : **3*x* - 2*y* - 2*k* = 0

putting *x* = 4, *y* = -5, we get,

3 × 4 - 2 × (-5) - 2*k* = 0

⇒ 12 + 10 - 2*k* = 0

⇒ 22 - 2*k* = 0

⇒ 2*k* = 22

⇒ *k* = 22/2 = 11

**
**

**on putting x=4,y= ^{-}5 in the equation 3x-2y-2k=0 then the value of k is wat**

**Given : **3*x* - 2*y* - 2*k* = 0

putting *x* = 4, *y* = -5, we get,

3 × 4 - 2 × (-5) - 2*k* = 0

⇒ 12 + 10 - 2*k* = 0

⇒ 22 - 2*k* = 0

⇒ 2*k* = 22

⇒ *k* = 22/2 = 11

**
**

What are you looking for?